The Role of Dream Affect in Waking Emotional Reactivity and Emotion Regulation: An EEG Study - Lin, Enyu (My University, 2021)
Emotion is a significant component of both waking life and dreaming. However, few studies have directly examined how emotions in both mental states correlate with each other with neuroscientific methods. This thesis investigated the relationship between dream affect and waking emotional reactivity and emotion regulation by measuring brain activities with electroencephalography (EEG). The late positive potential (LPP)—a sustained positive electrocortical response that maximizes at centroparietal regions—was adopted as a neural index of both emotional processes. Daily home dream diaries were obtained from 42 healthy young adults to measure their average (negative and positive) dream affect and sleep quality (as a control factor) during the seven days preceding the EEG session. During the EEG recording, the participants were presented with negative and neutral pictures and instructed to either (1) look at the pictures and feel naturally or (2) downregulate negative emotions elicited by the pictures. Afterward, each picture was rated according to its valence and arousal levels by the participants. The behavioral ratings and LPP results both demonstrated a link between dream affect and emotional reactivity and emotion regulation in wakefulness. In general, participants with higher levels of negative dream affect (or lower levels of positive dream affect) and good sleep quality showed greater emotional reactivity to negative pictures and ineffective emotion regulation while awake. However, this relationship was reversed for those with bad sleep quality. Therefore, the findings do not fully support continuity across dream affect and waking emotions (argued by the continuity hypothesis of dreaming). Also, the results do not fit well with the emotion regulation theories, which predict that negative dream affect aids emotion regulation. Instead, the threat-simulation theory seems to provide a more suitable explanation for the link between dream affect and waking emotional processing with regard to both good and bad sleep quality.
Keywords: dream affect, emotional reactivity, emotion regulation, late positive potential